2020
DOI: 10.1101/2020.12.17.423349
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recovery of neural dynamics criticality in personalized whole brain models of stroke

Abstract: The critical brain hypothesis states that biological neuronal networks, because of their structural and functional architecture, work near phase transitions for optimal response to internal and external inputs. Criticality thus provides optimal function and behavioral capabilities. We test this hypothesis by examining the influence of brain injury (strokes) on the criticality of neural dynamics estimated at the level of single subjects using whole-brain models. Lesions engendered a sub-critical state that reco… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 130 publications
5
15
0
Order By: Relevance
“…While it is well established that neuromodulation can be used to improve functional recovery in stroke patients (Blicher et al, 2009;Romero Lauro et al, 2014), we suggest that a deeper understanding of its effects not only in excitability, but also FC, is essential to unlocking the full potential of these rehabilitation procedures. In addition, the use of adaptive systems, such as the Rehabilitation Gaming System (RGS) (Cameirão et al, 2010), has been shown to engage widespread areas across the human cortex (Prochnow et al, 2013) and stimulate cortical reorganization of motor networks (Ballester et al, 2017), being a further potentiator of FC recovery.…”
Section: Tying Excitatory-inhibitory Homeostasis and Functional Reorganization In Stroke Recoverymentioning
confidence: 87%
See 3 more Smart Citations
“…While it is well established that neuromodulation can be used to improve functional recovery in stroke patients (Blicher et al, 2009;Romero Lauro et al, 2014), we suggest that a deeper understanding of its effects not only in excitability, but also FC, is essential to unlocking the full potential of these rehabilitation procedures. In addition, the use of adaptive systems, such as the Rehabilitation Gaming System (RGS) (Cameirão et al, 2010), has been shown to engage widespread areas across the human cortex (Prochnow et al, 2013) and stimulate cortical reorganization of motor networks (Ballester et al, 2017), being a further potentiator of FC recovery.…”
Section: Tying Excitatory-inhibitory Homeostasis and Functional Reorganization In Stroke Recoverymentioning
confidence: 87%
“…Pharmacological potentiation of AMPA receptors, in turn, has proved detrimental when applied at early stages, while a later application improved recovery, further supporting the delayed, long-term effect of these changes in excitability (Clarkson et al, 2011). Neuromodulation provides another option (Hummel and Cohen, 2006), and noninvasive techniques such as transcranial direct current (tDCS) and magnetic stimulation (TMS), aimed at increasing cortical excitability have been used to improve recovery in stroke patients (Blicher et al, 2009;Romero Lauro et al, 2014). An example of such techniques is theta burst stimulation (TBS) (Huang et al, 2005), based on the application of high frequency bursts of magnetic stimulation at intervals consistent with theta frequencies (i.e., ∼200 ms).…”
Section: Diaschisis and Excitabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Recent numerical studies highlighted how the topological details of the underlying network are crucial in shaping the type of the transition. Indeed, for densely connected networks the system exhibits a first order discontinuous transition [34,35], with the activity of the network jumping discontinuously between a quiescent and an overactive phase, while for sparse networks the transition disappears [34,36], suggesting that brain dynamics in individuals affected by stroke will not be critical [37]. Nevertheless, an analytical understanding of such critical transition, and thus the disentangling of the role of the connectome structure, criticality and emergent properties is still missing.…”
Section: Introductionmentioning
confidence: 99%